Predictors of Irregularities in PMTCT / eMTCT Service Attendances in Samia Bugwe North: Health Facility Study - Busia - Uganda - Francis, WABWIRE Paul; Evarine, NAMPEWO (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
011) and long waiting time (P-value = 0.03) were significantly associated with irregular attendance in the service. The prevalence of irregular attendance (43.75%) was however lower than 54% of [13] although, in agreement with [18] who rated maternal adherence to preventive drug regimens at time of delivery that varied widely across sites between 35% and 93.5%. The qualitative section used open-ended in-depth interview. The quotes were used in report to complement the findings of quantitative data. The results were that education, distance, economic status and male involvement were highly associated with irregularities in PMTCT / eMTCT attendance.